Prevalence of Impacted and Transmigrated Canine among Palestinian People -Jenin District. (Journal of Basic and Applied Research in Biomedicine, 2022)
The purpose of this study was to investigate the incidence of impacted maxillary canines in a Palestinian population. The study consisted of a retrospective analysis of the panoramic records of 1683 patients. Statistical analysis was used to examine potential differences in the distribution of impacted maxillary and mandibular canines stratified by gender, location (left or right), unilateral and bilateral position, and presence of transmigration. It was found that the incidence of impacted canines was (2.9%). Of the 54 impacted canines, 30 were in females and 24 were in male patients. Ages were in the range of 16-47. Of these subjects, 38 (84.44%) had unilaterally impacted maxillary canines, while 7 (15.55%) had bilateral impactions. One case of transmigrated canine was recorded among the whole sample. As has been noted the incidence of impacted canines in the sample Palestinian population was (2.9%) which is comparable to the findings from previous studies.